STRATEGI DAN TEKNIK PEMBERDAYAAN MASYARAKAT PADA USAHA ANYAMAN ROTAN SINTETIS - Virda Sulistiawati (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2020)
Local craft is one of the cultural identities in the global market that can provide differentiation and self-expression. one of the interesting fields to be discussed is the Sri Mulya artisans group. that this group seeks to empower the community through concrete solutions that can be implemented in Tambang Ayam Village, Anyar District, Serang Regency. Based on the above background, the formulation of the problem of this thesis are: 1) How are the efforts to empower the craftsmen community in improving economic welfare through synthetic rattan training? 2) What are the supporting and inhibiting factors in community empowerment efforts in improving economic welfare through synthetic rattan training? This study aims: 1) To find out about efforts to empower the craftsmen community in improving economic welfare through synthetic rattan training. 2) To find out the supporting and inhibiting factors in community empowerment efforts in improving economic welfare through synthetic rattan training. In this study I used qualitative methods and data collection techniques using observation, interviews and documentation. Based on the research that has been done, it can be concluded that community empowerment through this synthetic rattan wicker business uses several stages, including: the preparatory stage, the assessment stage, the alternative planning stage, the plan formulation stage, the implementation and mentoring stage, the evaluation stage, and the termination stage. Based on the research conducted it can be concluded that community empowerment through the activities of the Sri Mulya group is in terms of economic income increasing, socially namely opening up employment opportunities, reducing unemployment and better established social relations. As for the inhibiting factors in the craft of woven bamboo and synthetic rattan in the Sri Mulya group that is lacking in marketing.